The global status and hotspots of research in the field of trans-oral endoscopic thyroidectomy (TOET) from 2008 to 2022 - Li, Ping; Qin, Hao; Jin, Rui; Zheng, Wuping; Fan, Pingming; Lyu, Peng-fei (Frontiers in Surgery, 2023)
Purpose: In this study, the aim was to comprehensively analyze the current status, hotspots, and trends of trans-oral endoscopic thyroidectomy (TOET) through bibliometric analysis and by presenting the field atlas. Methods: Web of Science core collection database was adopted to screen studies regarding TOET published between September 1, 2022. The evaluation covered the criteria (e.g., total number of studies, keywords, and contributions from countries/regions, institutions, journals, and authors). Results: A total of 229 studies were covered. SURGICAL ENDOSCOPY AND OTHER INTERVENTIONAL TECHNIQUES is the largest publication in the field of TOETVA since 2009. The three countries that contributed the most studies were Korea, China, and the USA. The most frequently occurring core keywords in the field of TOET are vestibular approach, outcomes, experience, safety, robotic thyroidectomy, scar, video-assisted thyroidectomy and quality-of-life. The seven clusters generated in this study intraoperative monitoring of the laryngeal return nerve (# 0), learning curve (#1), postoperative quality of life (# 2), Central lymph node dissection and safety (# 3), complications (# 4), transoral vestibular pathway is minimally invasive surgery (# 5), and robotic surgery (# 6). Conclusion: The main research topics in the field of TOET place focuses on learning curves, laryngeal nerve monitoring, carbon dioxide gas bolus, chin nerve injury, surgical complications, and surgical safety. In the future, more academics will focus on the safety of the procedure and reduce the number of complications.